Leishmania guyanensis M4147 as a new LRV1-bearing model parasite: Phosphatidate phosphatase 2-like protein controls cell cycle progression and intracellular lipid content - Zakharova, Alexandra; Albanaz, Amanda T S; Opperdoes, Fred R; Škodová-Sveráková, Ingrid; Zagirova, Diana; Saura, Andreu; Chmelová, Lˇubomíra; Gerasimov, Evgeny S; Leštinová, Tereza; Bečvář, Tomáš; Sádlová, Jovana; Volf, Petr; et al. (PLoS neglected tropical diseases, 2022)
Leishmaniasis is a parasitic vector-borne disease caused by the protistan flagellates of the genus Leishmania. Leishmania (Viannia) guyanensis is one of the most common causative agents of the American tegumentary leishmaniasis. It has previously been shown that L. guyanensis strains that carry the endosymbiotic Leishmania RNA virus 1 (LRV1) cause more severe form of the disease in a mouse model than those that do not. The presence of the virus was implicated into the parasite's replication and spreading. In this respect, studying the molecular mechanisms of cellular control of viral infection is of great medical importance. Here, we report ~30.5 Mb high-quality genome assembly of the LRV1-positive L. guyanensis M4147. This strain was turned into a model by establishing the CRISPR-Cas9 system and ablating the gene encoding phosphatidate phosphatase 2-like (PAP2L) protein. The orthologue of this gene is conspicuously absent from the genome of an unusual member of the family Trypanosomatidae, Vickermania ingenoplastis, a species with mostly bi-flagellated cells. Our analysis of the PAP2L-null L. guyanensis showed an increase in the number of cells strikingly resembling the bi-flagellated V. ingenoplastis, likely as a result of the disruption of the cell cycle, significant accumulation of phosphatidic acid, and increased virulence compared to the wild type cells.
Keywords: leishmanióza kožní; Phosphatidate Phosphatase; Leishmania guyanensis; myši; zvířata; Leishmaniavirus; Leishmaniasis, Cutaneous; fosfatidátfosfatasa; Parasites; Mice; Animals; Cell Cycle; buněčný cyklus; paraziti; lipidy; Lipids